Analisis Pembiayaan Modal Usaha, Manajemen Keuangan, dan Pendampingan Usaha pada Pengembangan Usaha Nasabah Bank BTPN Syariah - Anggun Yuliana; Elmira Febri Darmayanti; Angga Kurniawan (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the role of working capital financing, financial management, and business assistance in the business development of BTPN Syariah Bank customers in Way Jepara, East Lampung. This research employed a qualitative descriptive method. The population consisted of 200 active customers, and a sample of 67 respondents was determined using the Slovin formula with a 10% margin of error. Data collection techniques included observation, interviews, questionnaires, and documentation. Data analysis followed the Miles and Huberman model: data reduction, data display, and conclusion drawing. The results indicate that working capital financing, financial management, and business assistance contribute positively to the business development of customers, particularly in increasing income, financial independence, and sustainable business growth.